The impacts of U.S. horse slaughter plant closures on a western regional horse market - Taylor, Mykel R.; Sieverkropp, Elizabeth (My University, 2014)
This study quantifies the price impacts from the closure of all U.S. horse slaughter plants in 2007 on live horses at a Montana auction. The hedonic pricing model includes supply and demand factors such as horse-specific characteristics, spatial and time effects, the U.S. economic downturn beginning in 2008, and slaughter plant closures. The hedonic model was estimated using a quantile regression, which revealed price declines of 12% to 16% for horses priced at or below $1,500 per head attributable to the end of U.S. horse slaughter.
Keywords: Horses; Slaughter; Quantile regression